2018
DOI: 10.1038/s41467-018-05399-8
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of cooperativity in the spin transition of an iron(II) complex on a graphite surface

Abstract: Cooperative effects determine the spin-state bistability of spin-crossover molecules (SCMs). Herein, the ultimate scale limit at which cooperative spin switching becomes effective is investigated in a complex [Fe(H2B(pz)2)2(bipy)] deposited on a highly oriented pyrolytic graphite surface, using x-ray absorption spectroscopy. This system exhibits a complete thermal- and light-induced spin transition at thicknesses ranging from submonolayers to multilayers. On increasing the coverage from 0.35(4) to 10(1) monola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
122
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(138 citation statements)
references
References 65 publications
(79 reference statements)
10
122
0
2
Order By: Relevance
“…Earlier studies have suggested that the mechanism of the SOXIESST effect is analogous to that of the LIESST effect [19,21,22,35]; their similarities and differences were discussed by V. Davesne et al [21,27,36]. Namely, the light or X-ray introduction leads to an excitation of the system from the LS ground state configuration to the excited state configurations and it follows that the excited state configurations decay into a metastable spin triplet HS configuration (intersystem crossing).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Earlier studies have suggested that the mechanism of the SOXIESST effect is analogous to that of the LIESST effect [19,21,22,35]; their similarities and differences were discussed by V. Davesne et al [21,27,36]. Namely, the light or X-ray introduction leads to an excitation of the system from the LS ground state configuration to the excited state configurations and it follows that the excited state configurations decay into a metastable spin triplet HS configuration (intersystem crossing).…”
Section: Introductionmentioning
confidence: 97%
“…For instance, XAS at Fe L 2,3 -edge utilizes the electronic excitation from the 2p core level to the 3d unoccupied state following the X-ray perturbation. Previous Fe L 2,3 -edge XAS studies on a representative SCO molecule, Fe(phen) 2 (NCS) 2 at low and high temperatures, have established a set of spectroscopic fingerprints for the HS and LS states [32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9][10][11] Considerable effort has been made to prepare such complexes on surfaces, e. g. for electrical contacting. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] To enable physical vapor deposition, which is the most common technique for obtaining high-quality films, compounds with increased thermal stability have been synthesized. However, even for such robust compounds, fragmen-tation issues have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The surface/interface energy can be therefore viewed as a key parameter, which governs the SCO properties at the nanoscale . Understanding surface/interface phenomena is not only important to elucidate nanoscale SCO behaviors but also opens up possibilities for engineering these nanomaterials . However, thin films and nanostructures usually have nonuniform properties due to defects, grain boundaries, strain distributions, and so forth.…”
Section: Comparison Of Reported Elastic Moduli Ofmentioning
confidence: 99%